1 Peter a critical and exegetical commentary : volume 2: chapters 3-5 - Horrell, David G. 1963-; Williams, Travis B. 1980- (London T&T Clark, 2023)
The second volume in Travis B. Williams' and David G. Horrell's magisterial ICC commentary on first Peter. Williams and Horrell bring together all the relevant aids to exegesis - linguistic, textual, archaeological, historical, literary, and theological - to help the reader understand the letter. This second covers the major part of the letter, providing commentary on 2.11 to the end of the letter. The exegesis provides for each passage sections on bibliography, text-criticism, literary introduction, detailed exegesis, and overall summary. The volume concludes with a comprehensive bibliography, which covers the whole epistle
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible -- Commantaries; Bible -- Study and Teaching; Biblical studies & exegesis; Kommentar